Representing and accounting for the expulsion of the Sephardic Jews in contemporary Spanish historical fiction. Issue 2 (4th May 2017) - Gilmour, Nicola
ABSTRACT: The expulsion of the Jews from the Christian kingdoms of Castile and Aragon in 1492 by Isabel I of Castile and Fernando II of Aragon is an event from Spain's mediaeval past that continues to stimulate scholarly controversy. It is one of the most sensitive issues in Spanish historiography, alongside the Spanish Civil War (1936–1939). This paper examines the portrayal of the expulsion in four Spanish historical novels published around the turn of the millennium that narrate the events from the perspective of Jews and conversos . It asks how the events of the expulsion have been reinterpreted in fiction to incorporate the perspective of the victims, particularly in light of the changing historiography after Spain's transition to democracy in the early 1980s and the commemorations of 1992 (the 500th anniversary of the expulsion) which stimulated interest in Spain's tricultural past. The essay looks particularly at how writers of historical fiction represent and account for the expulsion of the Jews, and examines the contribution these novels make to the reintegration of the memory of this group into the Spanish collective memory.